Isolation of fungi from dead arthropods and identification of a new mosquito natural pathogen. Issue 1 (December 2016) - Jaber, Sana; Mercier, Alex; Knio, Khouzama; Brun, Sylvain; Kambris, Zakaria
Abstract Background Insects are well known vectors of human and animal pathogens and millions of people are killed by mosquito-borne diseases every year. The use of insecticides to target insect vectors has been hampered by the issues of toxicity to the environment and by the selection of resistant insects. Therefore, biocontrol strategies based on naturally occurring microbial pathogens emerged as a promising control alternative. The entomopathogenic fungusBeauveria bassiana is well characterized and have been approved by the United States Environmental Protection Agency as a pest biological control method. However, thousands of other fungi are unexploited and it is important to identify and use different fungi for biocontrol with possibly some vector specific strains. The aim of this study was to identify new fungal entomopathogens that may be used as potential mosquito biocontrol agents. Methods Cadavers of arthropods were collected from pesticide free areas and the fungi associated isolated, cultured and identified. Then the ability of each isolate to kill laboratory insects was assayed and compared to that ofB. bassiana . Results In total we have isolated and identified 42 fungal strains from 17 different arthropod cadavers. Twenty four fungal isolates were cultivated in the laboratory and were able to induce sporulation. When fungal spores were microinjected intoDrosophila melanogaster, eight isolates proved to be highly pathogenic while the remaining strains showed moderate or no pathogenicity. Then a selection of isolates was tested againstAedes mosquitoes in a model mimicking natural infections. Only one fungus (Aspergillus nomius ) was as pathogenic asB. bassiana and able to kill 100 % of the mosquitoes. Conclusion The obtained results are encouraging and demonstrate the feasibility of this simple approach for the identification of new potential mosquito killers. Indeed, it is essential to anticipate and prepare biocontrol methods to fight the expansion of mosquitoes' habitat predicted in certain geographical areas in association with the occurring climatic changes.